Visual plumes coastal dispersion modeling in southwest Sabah - Zainudin, Zaki (Academic Journals, 2011)
The visual plumes model encompassing the DKHW (Davis, Kannberg, Hirst model for Windows) and Update Merge (UM3) sub-models were utilized in the modeling exercise. In theory, the dilution capacity of open waters, particularly coastal areas, straits and oceans are enormous. This means that for surface and sub-merged point source discharges, the effluent concentration (Ce) will cause insignificant change in the overall ambient water quality. Instead, Ce will eventually reach Ca (ambient concentration) over a spatial distance (vertical and horizontal). This distance is of interest with regards to water quality preservation efforts as the macro level distribution effects of the pollutant species in question can be determined. The travel distance (l t) is a main function of ambient current velocity (m/s) and direction. Prior to the modeling exercise, field data pertaining to ambient water quality, hydraulic characteristics and tide patterns were collected. The modeling results indicated that there was no significant change in ambient concentration for all constituents modeled when the effluent discharge was increased from 1,500 m3/h to 2,400 m3 /h, as long as the current quality was maintained. The plume travel distance would also not entrain into foreign waters as long as proposed volumetric discharge rate is no violated.